The determination of metal content, microbial contamination and dissolution assessment of the ethanol extract of pasak bumi root - Nurani, Laela Hayu; Kumalasari, Eka; Zainab, Zainab; Mursyidi, Achmad; Widyarini, Sitarina; Rohman, Abdul (Universitas Ahmad Dahlan, 2017)
The Eurycoma longifoliais bitter therefore, to address this problem, it is prepared in a capsule form. The capsule dosage form must has the parameters of good quality, thus expected to increase the potential use of biodiversity and the interest of the community in consuming the medicine from the natural materials. The purpose of this research is to get the capsule product of ethanol extract of the Eurycoma longifolia root of quality through the test of total plate value and yeast yeast contamination, the determination of the metal content of Pb, Hg, Cd and the level of flavonoids released in the capsule dissolution test of ethanol extract Eurycoma longifolia root. The result of this research shows that the dissolution efficiency (DE120) capability of ethanol extract of Eurycoma longifolia root is 81,04±2,38%. Test of heavy metal content in capsule of of ethanol extract of Eurycoma longifolia root found level of Pb equal to 4,132 ppm and not detected content of Cd and Hg in capsule. This indicates that the capsule meets the requirements set by BPOM RI. Tests for total plate numbers (ALT) and yeast capsule ethanol extract of the E. longifolia root were each obtained data of 70 x 102 colonies / g and 4 x 102 colonies / g. It also shows that the capsules meet the requirements by BPOM RI.